Methodologies for effectively assessing complementary and alternative medicine (CAM) : research tools and techniques - Langweiler, Mark J.; McCarthy, Peter W.; Leight, Kenneth A. (Singing Dragon, 2015)
Examining the methods and criteria for assessing Complementary and Alternative Medicine (CAM), this book highlights how CAM research must be treated differently to research in conventional medicine. Experts from a wide range of CAM modalities provide background to the therapies and suggest the most effective research methodology for each.